Enhancing 10-HDA production of Escherichia coli by heterologous expression of MexHID transporter proteins - Ziting Xu; Chaofan Du; Sheng Gao; Xinrui Yan; Pan Deng; Yuehan Liu; Junqing Wang; Junqing Wang; Ruiming Wang; Ruiming Wang; Nan Li; Nan Li (Frontiers in Bioengineering and Biotechnology)
10-Hydroxy-2-decenoic acid (10-HDA) is a medium-chain α,β-unsaturated carboxylic acid that exists in royal jelly with terminal hydroxylation. It has a broad market value because of its antibacterial, anti-inflammatory, anti-tumor, anti-radiation, and other active functions. The one-step whole-cell catalytic synthesis of 10-HDA by constructing engineered strains has improved the reaction rate to a certain extent compared with the previous two-step method. However, the accumulation of 10-HDA to a certain concentration in engineered Escherichia coli strains will damage the structure and function of cells and even lead to death; this unique antibacterial and antimicrobial activity seriously constrains the production of 10-HDA. In this study, we mined a transporter protein from Pseudomonas aeruginosa, which possesses the ability to efficiently efflux 10-HDA, and constructed a transporter protein overexpression strain by using the multicopy chromosome integration technique, which further improved the efficiency of product efflux, weakened the feedback inhibition of 10-HDA to a certain degree, and increased the substrate conversion rate to 88.6%. 10-HDA was synthesized up to 0.94 g/L by the replenishment flow-addition technique, providing a simple and efficient pathway for the yield breakthrough of 10-HDA biosynthesis.